Graphene as a replacement for Si in nano-electronics - Khan, Raisa Tamanna (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.